IMPLEMENTASI ALGORITMA MODIFIKASI BROYDEN-FLETCHER-GOLDFARB-SHANNO (MBFGS) (Universitas Dr. Soetomo, 2016)
The concept of minimum resolving set has proved to be useful and or related to a variety of fields such as Chemistry, Robotic Navigation, and Combinatorial Search and Optimization. Two graph are path graph (????????) anf circle graph (????????). The corona product ???????? ⨀???????? is defined as the graph obtained from ????????and ???????? by taking one copi of ???????? and ????1copies of ???????? and joining by an edge each vertex from the ????????ℎ copy of ???????? with the ????????ℎ vertex of ????????. ???????? ⨀ ???????? and ????????⨀???????? not commute to ????≠????, it is showed that order of graph ???????? ⨀ ???????? different with graph ????????⨀????????. Based on research obtained ????????????(????????⨀????????)=????.????????????(????1,????) dan ????????????(????????⨀????????)=????.???????????? (????1+????????)Keyword : Resolving Sets, Metric Dimension, Path Graph, Circle Graph, Corona Graph